Pemanfaatan Twitter Sebagai Media Penyebaran Informasi Oleh Dinas Komunikasi dan Informatika - Fauzi Solihin; Siti Awaliyah; A. Muid Aris Shofa (FKIP, Universitas Palangka Raya, 2021)
This study aims to discuss the types of information services, the procedures for the delivery of information services, the obstacles faced in providing information services. The approach used is qualitative descriptive research. Sources of data in this study are divided into primary and secondary data sources. Data collection was carried out using several techniques, namely observation, interviews, and document study. The type of information disseminated by Twitter is information about government policies, public services, health, traffic, culture, natural disasters, current phenomena and other information that is of public interest. The procedure for using Twitter as an information medium is by the Communication and Information Technology Office consisting of 4 stages, namely: collecting information data from related agencies, processing data, making designs, publishing, evaluating to check the correctness of published information. Supporting factors using Twitter, namely the information conveyed quickly spreads, reaches many people, and is easy to use. The problem with using Twitter as a provider of information is coordination between managers. lack of coordination with related agencies, and limited number of managers.